ANALISIS FAKTOR DETERMINASI KREDIT SECARA LANGSUNG DAN TIDAK LANGSUNG DI KABUPATEN BERAU - Amiruddin, . (Jurnal Ekonomi Pembangunan, 2013)
The purpose of this study is to (1) analyze the effect of per capita income, inflation, interest rate, savings last year and the savings directly to credit in Berau. (2) analyze the effect of per capita income, inflation, interest rate, savings last year and the savings indirectly to credit in Berau. (3) analyze which variables are dominant influence on credit in Berau Disrict. In order to test the hypothesis analysis the authors use analytical tools path analysis using SPSS 19. The data used in this study is the data per capita income, inflation, interest rate, savings and credit in 2002-2012. The results show that there is a direct influence between per capita income, inflation, interest rate, savings last year and the savings to credit in Berau District, and The results show that there is a indirect influence between per capita income, inflation, interest rate, savings last year and the savings to credit in Berau